An ethnopharmacological study of aromatic Uyghur medicinal plants in Xinjiang, China - Lu Zhao; Shuge Tian; E. Wen; Halmuart Upur (Pharmaceutical Biology, 2017)
Context: An ethnobotanical survey was completed in a remote village and surrounding country of Xinjiang, where most Uyghur medicinal plants could be collected. This work clarifies and increases ethnobotanical data. Objectives: We surveyed and organized aromatic medicinal plants that are commonly used in clinical settings to provide a significant reference for studying new medical activities. Materials and methods: In the survey, informants who have traditional knowledge on aromatic Uyghur medicinal plants were interviewed between March 2014 and September 2014. Aromatic medicinal plant species and pertinent information were collected. Some therapeutic methods and modes of preparation of traditional aromatic medicinal plants were found. Results: A total of 86 aromatic medicinal plant species belonging to 36 families were included in our study. We identified 34 plant species introduced from different regions such as Europe, India and Mediterranean areas. Fruits and whole plants were the most commonly used parts of plant, and most aromatic medicinal plants could be applied as medicine and food. We assigned the medicinal plants a use value (UV). Knowing the UV of species is useful in determining the use reliability and pharmacological features of related plants. Conclusions: Xinjiang is an area in which indigenous aromatic medicinal plants are diversely used and has therefore established a sound dimensional medical healthcare treatment system. Some aromatic Uyghur medicinal plants are on the verge of extinction. Hence, further strategies for the conservation of these aromatic medicinal plants should be prioritized.